Role of computed tomography in diagnosis of bronchiectasis. Issue 4 (April 1987) - Cooke, J C; Currie, D C; Morgan, A D; Kerr, I H; Delany, D; Strickland, B; Cole, P J
Abstract : Bronchograms and computed tomograms were performed in 27 patients who presented consecutively for bronchography with chronic sputum production. The films were reported separately by three consultant radiologists, who had been asked to give a diagnostic interpretation of the films for each bronchopulmonary segment. The reporting of bronchiectasis on computed tomograms was compared with that on bronchograms. The sensitivity and specificity of computed tomography at segmental level compared with bronchography was 66% and 92%, respectively. We conclude that computed tomography alone is not yet suitable for accurate characterisation and localisation of disease in patients in whom surgery is contemplated. Computed tomography may be useful in patients in whom bronchography is contraindicated and for monitoring progression of disease after initial combined computed tomography and bronchography.